Faktor Risiko Anemia pada Wanita Pemetik Teh - Setyorini, Eryasih; Anwar, Faisal; Riyadi, Hadi; Khomsan, Ali (Media Kesehatan Masyarakat Indonesia, 2019)
Anemia is known as a public health problem for many years, based on the results of Riskesdas 2018 it is known that the prevalence of anemia is 48.9%. This research aims to analyze the risk factors that influence anemia in female tea pickers in Pangalengan, Bandung, West Java. The research method was cross-sectional with 148 subjects of the so-called Wanita Usia Subur (WUS). They are women of childbearing age, between 18-45 years old who were married and not pregnant. They were selected purposively in the plantation areas Purbasari, Talun Santosa and Sedep. This research was part of a research funded by Neys-van Hoogstraten Foundation (NHF). The data obtained are the characteristics of the subjects (age, family size, length and level of education), monthly family expenses for food and non-food, status of nutrition and body composition, and anemia status. The results showed that most of the female tea pickers are 40-44 years old, having family size up to 4 people and 72.3% of them are low level educated (89.9% has maximum the elementary school education). The average expenses for non-food are greater than those for food. Based on various body composition indicators, the female tea pickers were in general overweight (56.8%), normal upper arm circumference (98.6%). The average total of body fat is greater than 32,1%, normal visceral fat (≤9%), waist circumference at risk ≥80 cm, and RPP ≥0.8 cm at 81.1%. The prevalence of anemia in tea picking women was 42.6%. Overweight is the most risk factor for anemia because fat accumulation can reduce iron absorption so that the amount of hemoglobin goes down and erythrocytes decreases. The age as a protective factor. Anemia can be prevented through nutrition education, healthy lifestyles, and controlling the causes and predisposing factors.